Melhoria da qualidade química do perfil do solo como estratégia para atenuar os efeitos de déficits hídricos sobre a produtividade das culturas de grãos em sistema plantio direto - Dalla Nora, Douglas (2014)
The chemical improvements provided by no-till have been restricted to the upper soil layers, limiting root development in the subsurface, and the efficient use of water, especially in years with drought. This study had the aim assesse: I- characterize the effects of the isolated use of gypsum or combined with lime on the soil chemical properties and crop grain yield in SPD; II- evaluate the effect of chemical improving layer rooting on the crop yield in SPD under induced water deficit. Four experiments were conducted in Oxisols dystrophic managed under continuous NT in Rio Grande do Sul State, with distinct chemical quality in rooting layer, from 2009 to 2014. The experimental design was randomized block with three replications. Two experiments were established in 2009 in Carazinho with treatments ranging 0.0 to 6.5 Mg ha-1 gypsum. In one experiment the plots were divided into two subplots without restriction and with 30% of the rainfall for the implementation of exclusion chamber. Two other experiments were implanted in São Miguel das Missões and Tupanciretã in 2011. In São Miguel das Missões used a randomized block design with split plots, the main plots with lime rates ranging from 0.0 to 5, 0 Mg ha-1, and the subplots composed by no lime treatment at a dose of 2.0 Mg ha-1. In Tupanciretã, the experiment was comprised of a 4x4 factorial design, with four levels of gypsum ranging from 0.0 to 6.0 Mg ha-1, and four liming levels ranging from 0.0 to 4.8 Mg ha-1. The soil samples were made in the stratified layer of 0.00 to 0.60 m. There was an increase in the Ca and S in the entire profile, and reduce the Al saturation and an increase in basis saturation and the saturation of Ca over time. In response to improving the quality of chemical rooting layer was found increased yield of soybean, corn and wheat. With crop rotation during the summer, the sample layers in which there was related to productivity stood at greater depth (0.25-0.40 m layer for the first experiment and 0.00 to 0.40 m for Experiment II). No crop rotation in summer the sample layers that were associated with productivity were located closer to the surface (layer from 0.00 to 0.10 m for Experiment III and 0.00 to 0.25 m for the experiment IV). An increase in base saturation and reduction in Al saturation throughout the EC with of isolated gypsum rates or combined to lime. The increase in the amount of grain produced per mm of rain, resulting from the application of gypsum, was higher when there was water estress during the critical period of crop. The chemical improvement of soil rooting layer provided by the addition of gypsum attenuated the soybean yield loss associated with water restriction.